CEO compensation and risk-taking at financial firms: Evidence from U.S. federal loan assistance - Gande, Amar; Kalpathy, Swaminathan (Journal of Corporate Finance, 2017)
We examine whether risk-taking among the largest financial firms in the U.S. is related to CEO equity incentives before the 2008 financial crisis. Using data on U.S. Federal Reserve emergency loans provided to these firms, we find that the amount of emergency loans and total days the loans are outstanding are increasing in pre-crisis CEO risk-taking incentives – “vega”. Our results are robust to accounting for endogeneity in CEO equity incentives and selection of financial firms into emergency loan programs. We also rule out the possibility that our results are driven by a bank's funding base, bank complexity, CEO overconfidence, or matching of CEOs to select banks. We conclude that equity incentives (vega) embedded in CEO compensation contracts were positively associated with risk-taking in financial firms which resulted in potential solvency problems. We also find some evidence, although somewhat weaker, that higher incentive alignment (“delta”) mitigated such problems in those financial firms.